Web Development for Resource-Based Learning Model in English Learning for 10 Grade - Muzainuddin, Moh; Setyosari, Punaji; Kuswandi, Dedi (Universitas Negeri Malang, 2024)
The development of technology in the world of education can not be separated. This is related to the use of learning media as a learning resource. In this era, teachers and students are required to be able to understand and use technology as a learning medium. In this regard, the use of learning media that connected to the internet, especially web-based learning media for students in class X MA. The purpose of this research is to produce web-based learning media products with the Resource Based Learning model in improving English learning skills.This research uses the Lee & Owens development model which consisted of five stages: assessment/analysis, design, development, implementation, and evaluation. Furthermore, after this media is developed, the next stage goes through a validation process by experts, and is tested to learners regarding the attractiveness and effectiveness of web-based online media. The result of this research has fulfilled the validity of data analysis from media experts and material experts and increasing student learning outcomes. Abstrak Pengembangan teknologi dalam dunia pendidikan tidak dapat dipisahkan. Hal ini berhubungan dengan penggunaan media belajar sebagai sumber belajar. Pada era zaman ini, guru dan peserta didik diwajibkan untuk dapat memahami dan menggunakan teknologi sebagai salah satu media pembelajaran. Berkaitan dengan hal tersebut, penggunaan media pembelajaran yang terhubung dengan internet khususnya media pembelajaran berbasis web untuk peserta didik di kelas X MA. Tujuan penilitian ini adalah untuk menghasilkan produk media pembelajaran berbasis web dengan model Resource Based Learning dalam meningkatkan kemampuan belajar Bahasa Inggris. Model penelitian menggunakan model pengembangan Lee & Owens yang terdiri dari lima tahap: penilaian/analisis, desain, pengembangan, implementasi, dan evaluasi. Selanjutnya, setelah media dikembangkan, tahap berikutnya melalui proses validasi oleh para ahli, dan diuji ke peserta didik mengenai kemenarikan dan keefektifan media berbasis web. Hasil penelitian ini memenuhi kevalidan hasil analisis data dari ahli media, ahli materi dan meningkatnya hasil belajar peserta didik.